Discovery of indolizines containing triazine moiety as new leads for the development of antitumoral agents targeting mitotic events. Issue 18 (15th September 2015) - Lucescu, Liliana; Ghinet, Alina; Belei, Dalila; Rigo, Benoît; Dubois, Joëlle; Bîcu, Elena
Graphical abstract: Abstract: A new family of 3-aroylindolizines bearing a dimethoxytriazine unit in their position 1 was designed, synthesized and evaluated for their ability to inhibit tubulin polymerization and cellular growth in vitro. Compound39 was the best candidate in the current study with a GI50 value of 870 nM on SNB-75 CNS cancer cells and of 920 nM on MDA-MB-231/ATCC breast cancer cells. The standard NCI Compare results indicated that indolizine39 may target PLK1 (polo-like kinase 1).